A battle without weapons. Charity and beneficense in the fight against medical knowledge. Lima: second half of the nineteenth century - Coello Rodríguez, Antonio (2019)
The following research work uses unpublished and edit sources to show the ideological struggle in Lima during the second half of the nineteenth century between the recently created Faculty of Medicine of Lima (San Fernando) for leading and organizing a struggle to sanitize up the hospitals and the city against the charitable entity of the Society of Public Charity of Lima, an institution that watched over the food, education and health of the sick and dispossessed, but that was protected in Christian charity and did not present any scientific contribution, only welfare represented by a community of affluent and wealthy people who give their goods for the maintenance of the needy classes. This ideological struggle will be supported, also, by the arrival of the Sisters of Charity, in Peru, who will be invited by the Charity Society to be in charge of hospitals and provide moral and spiritual help to the sick, having a direct confrontation with the doctors, which was reflected in newspapers and magazines of the time.